Optimization of ultrafiltration of cutting oil wastewater enhanced by application of twisted tapes: Response surface methodology approach - Popovic, Svetlana; Karadzic, Milica; Cakl, Jiří (Elsevier Science, 2019)
Enhanced ultrafiltration process as the cleaner treatment of cutting oil wastewater has been presented in this paper. Twisted tapes as turbulence promoters were used for fouling mitigation and the enhancement of cutting oil wastewater ultrafiltration for the first time. The response surface methodology was used for modelling and analysis of the most important effects, particularly an aspect ratio of twisted tape and cross-flow rate, on the flux and specific energy consumption as responses. The improved maximal flux under minimal specific energy consumption has been obtained by the optimization of twisted tape dimension alongside the working conditions. The application of twisted tapes remarkably increases the flux. The linear effects of the cross-flow rate and the aspect ratio have a dominant positive influence on the flux. The linear effect of cross-flow rate has a positive dominant effect on the specific energy consumption. The squared effect of the aspect ratio is statistically significant and allows for optimization. The optimal flux of 201 L m(-2) h(-1) can be reached under specific energy consumption of 1.34 kWh m(-3) with a twisted tape of the aspect ratio of 1.55 and 2% w/w oil concentration.
Optimalizace ultrafiltrace odpadní řezné olejové emulze intenzifikované využitím spirálových vestaveb: metodika odezvy povrchu
Keywords: Turbulence promoter; Fouling minimization; Membrane filtration; Response surface methodology; Process optimization; Promotory turbulence; minimalizace zanášení; membránová filtrace; RMS metodika; optimalizace procesu